"Feel the fear and do it anyway" … nursing students' experiences of confronting poor practice. (October 2021) - Jack, Kirsten; Levett-Jones, Tracy; Ylonen, AnnaMari; Ion, Robin; Pich, Jacqueline; Fulton, Roberta; Hamshire, Claire
Abstract: Aim: The two aims of this study were, first, to explore nursing students' experiences and perspectives of reporting poor care and second, examine the process by which they raised concerns. Background: The nursing literature is replete with studies which explore nursing students' experiences of clinical placement. However only a small number explore students experiences of challenging poor care and how this is enacted in the practice setting. Setting and participants: Fourteen nursing students from undergraduate pre-registration nursing programs across three universities, two in the United Kingdom (UK) and one in Australia. Design and analysis: This paper reports findings from narrative interviews about students' clinical experiences of reporting poor care. Data were audio recorded, transcribed verbatim and analyzed using a constant comparison approach. Emerging themes were identified, discussed and verified by the researchers. Results: Four montages from the narratives highlight the overarching themes: bullying, patient advocacy, lack of empathy and poor care. They demonstrate how, driven by an ethical imperative, students speak up when they witness poor care despite the difficulties of doing so: in some cases, the students in this study were prepared to continue speaking out even when initial concerns were dismissed. Conclusion: Both practice and university teams have a responsibility to support students' development as ethical and courageous practitioners, able to recognize when care falls below an acceptable standard. Highlights: This paper highlights the vital role that students play in highlighting poor nursing care practices. Nursing students are capable of reporting poor nursing care even when it might come at a cost to themselves. Clinicians and academics must support students to challenge poor nursing care practices.